PERBAIKAN NILAI KADAR AIR DAN INDEKS PLASTISITAS TANAH LEMPUNG LUNAK MENGGUNAKAN BAHAN TAMBAH EXPANDED POLYSTYRENE (EPS) DAN RESIDIUM CRACKING CATALYST 15 (RCC 15) - shaputra, muhammad rio eka; Syahril; Indra Noer Hamdhan; Geni Firuliadhim (Politeknik Negeri Semarang, 2025)
The uneven distribution of development in each region can result in construction on land with poor characteristics. One of the soils that has weak characteristics is soft clay. Soft clay has weak characteristics, such as relatively high water content and plasticity index (PI), so it needs to be stabilized to improve its bearing capacity before being used in construction. This study aims to examine the effect of adding Expanded Polystyrene (EPS) which is a fabricated material with Residium Cracking Catalyst 15 (RCC15) which is a waste product of oil processing from PT. Pertamina on improving the characteristics of soft clay. The specimens from Cililin, Bandung Regency, has a soft inorganic clay (CH) with a clay content of 61% and a water content of 37.945%. Test specimens were made with variations in the addition of EPS of 0.4% and RCC15 of 20%, 25%, and 30%. The results of the property index test showed that the addition of RCC15 can increase the water content and plasticity index (PI) value, with the optimum value at a mixture of 0.4% EPS and 25% RCC15. The impact of using EPS and RCC15 as additives has the potential to increase the stability of soft clay, making it suitable for use in construction.